Design And Analysis of Analog TRNG Using Sample and Hold Circuit - Aksshaya, B; Madhura L. V., G; S, Nivethashri; T, Vishnuvarthini; N, Mohankumar (International Journal of Engineering and Technology, 2018)
Implementation of analog True random number generators is inevitable in almost all the security applications and encryption protocols nowadays. Although many digital True Random Number Generators are available, we proposed a method of random number generation using analog module of mixed signals. In actual fact generation of True Random Numbers is by utilizing the sample and hold circuit which is controlled by another random clock source, and a post processing circuit for generation of unpredictable binary sequence of numbers. The primary input source is an analog signal, essentially highly random noise from the external environment. The high unpredictability, less resource and simple circuit design are some highlights of the proposed work. Finally, the randomness is evaluated using NIST test suites and results are plotted and analyzed.Â Â